The Constitutionalization of Budget for Education and Its Judicial Enforcement in Indonesia - Omara, Andy (The Constitutional Court of the Republic of Indonesia, 2016)
The introduction of provision concerning budget allocation for education in the amended constitution is not a common method in constitutional drafting in Indonesia. This article aims to understanding the background of the inclusion of this provision and its judicial enforcement. It argues that the establishment of this provision closely related to the fact that education was not properly funded. As a result, the quality of education was negatively affected. The constitutionalisation of budget for education opens the possibility to allocate the national budget in this field in a more sustainable way. In addition, by constitutionalizing budget for education, there is a legal avenue available to challenge the government policy if the government fails to fulfill its constitutional obligation. The newly established Constitutional Court has the power to review whether the allocation of national budget for education is consistent with the Constitution. In some judicial review cases on budget for education, the Court took legal approach and also extralegal factors in its rulings.